ANALISIS YURIDIS TERHADAP PERAN POLISI DALAM PENANGGULANGAN TINDAK PIDANA KDRT DI DITRESKRIMSUS POLDA SUMUT - NANCI YOSEPIN SIMBOLON (JURNAL ILMIAH KOHESI, 2020)
The study of the role of domestic violence investigation is raised given the process of investigation in this household, there are still many obstacles in the implementation. In this writing the problem is how the efforts to tackle domestic violence, the role of investigators in domestic violence and the barriers faced by investigators against domestic violence. Efforts in tackling acts of violence in households are by doing the pre-entip efforts by socializing to the community. In the case of violence in domestic investigators act to perform prepentif and respentive actions, where the respentif is to perform law enforcement process under the ACT NO. 22 year 2002 on police and based on criminal CODE and LAW NO. 23 year 2004 on the elimination of domestic violence. The prepentif is an investigation and investigation. Barriers to investigation in domestic violence, namely the lack of witnesses and lack of public response in household issues, so as not to be confused by other people or the police. According to the title of this research, the location of this research is in the unit of Poldasu. This research is done in normative juridical where here examine the application of the rules of law relating to law number 23 of year 2004. This research is also conducted by collecting data, conducting interviews with police investigators who are directly related to the domestic violence in this household, namely the Poldasu-based unit for the process of investigation of acts of violence in households. According to the results of the research of Poldasu-based units, the level of domestic violence is increasing year by year. The KUHAP investigation and the barriers found in this investigation process are the lack of responses from the community that considers the problem to be an internal problem in the family where the other person should not mix it.